How Immersion, Presence, Emotion, & Workload Differ in Virtual Reality and Traditional Game Mediums. (September 2018) - Lum, Heather C.; Greatbatch, Richard; Waldfogle, Grace; Benedict, Jacob
The gaming experience is a critical component in the development and evolution of games. This study aims to assess the differences between virtual reality and a more traditional gaming experience in levels of emotion, immersion, and presence. We know that virtual reality is changing the way that people play games, but the extent to which virtual reality creates a more immersive and more present environment is still largely debated. Most of us can feel a difference but where does it lie? Similarly, if we are indeed more immersed and present, does that impact our perceived workload and how we feel about the task? These questions are examined in more detail in this paper. Results of this study may help give statistical support to various factors that are related to the virtual reality experience. These findings may extrapolate to a larger context for training simulations for military applications as well as consumer domains.